The Activity of Nimba Leaves (Azadirachta Indica A. Juss.) Extract Insecticide as Vegetative Pesticide on Rice Weevil (Sitophilus Oryzae L.) (Coleoptera: Curculionidae) - I Wayan Suanda; Ni Made Delly Resiani (Warmadewa University Press, 2020)
The purpose of the research regarding The Activity of Nimba Leaves (Azadirachta Indica A. Juss.) Extract as Vegetative Pesticide on Rice Weevil (Sitophilus Oryzae L.) is to identify the characteristics of contact poison, pesticide, and antifeedan from Nimba leaves extract on rice weevil (S. oryzae L.). The research is conducted in the biology laboratory Faculty of MIPA University of Udayana. The period of the research is from April to August 2017, using the complete random framework with 6 concentration tests (10 ppm, 100 ppm, 1000 ppm, 10000 ppm, 100000 ppm concentration, and control using methanol pro analysis (PA) solvent). Each test is repeated 4 times. The data is analyzed using Analysis of Variance (ANOVA) and if there is a significant difference (P<0.05) it is followed by Duncan test to identify the difference between the different tests. The data is quantified using SPSS for windows release 12.5 the year 2003. The result indicates that the extract of Nimba leaves A. indica A. Juss. is behaving more as an antifeedan at an optimum concentration of 1000 pm during the observation 48 hours after the test. The crude extract of Nimba leaves at an optimum concentration of 1000 ppm and a maximum of 10000 ppm, during the observation 36 hours after the application, is leaning towards behaving as a contact poison to the S. oryzae L.